2014
DOI: 10.4025/actasciagron.v36i3.17791
|View full text |Cite
|
Sign up to set email alerts
|

<b>The effect of filter cakes enriched with soluble phosphorus used as a fertilizer on the sugarcane ratoons

Abstract: ABSTRACT. The objective of this work was to evaluate the effect of fertilization with filter cakes enriched with soluble phosphate on sugarcane ratoons. The experiment was performed from November 2007 to December 2009 at Presidente Prudente, São Paulo State, Brazil, in a completely randomized block design in a 4 x 4 factorial arrangement, with the first factor consisting of doses of filter cake (0, 1, 2 and 4 Mg ha -1) and the second doses consisting of phosphorus fertilizer (0, 50, 100, 200 kg ha -1 of P 2 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 10 publications
4
14
0
4
Order By: Relevance
“…Previous studies (Almeida Junior et al., ) have similarly reported a positive effect of FC applied to sugarcane, mainly through an increase in the levels of P, K and Cu in shoots. Moreover, FC addition has also been shown to influence various soil physical and chemical properties including, soil CEC, water retention capacity, soil aeration and reduced concentration of aluminium in soil (Korndörfer & Anderson, ; Santos et al., ; Torres, Sartori, Américo, & Ferreira, ). Collectively, this suggests that FC is an important organic amendment for ameliorating degraded soils and to provide plant nutrients, although the precise mechanisms associated with increased nutrient availability in soil, either directly or indirectly from FC, remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (Almeida Junior et al., ) have similarly reported a positive effect of FC applied to sugarcane, mainly through an increase in the levels of P, K and Cu in shoots. Moreover, FC addition has also been shown to influence various soil physical and chemical properties including, soil CEC, water retention capacity, soil aeration and reduced concentration of aluminium in soil (Korndörfer & Anderson, ; Santos et al., ; Torres, Sartori, Américo, & Ferreira, ). Collectively, this suggests that FC is an important organic amendment for ameliorating degraded soils and to provide plant nutrients, although the precise mechanisms associated with increased nutrient availability in soil, either directly or indirectly from FC, remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the interaction of FC and mineral P sources as a bio‐fertilizer management option to improve soil fertility for sugarcane production (Bokhtiar, Paul, & Alam, ; González, Prado, Hernández, Caione, & Selva, ; Santos, Silva, Tiritan, & Crusciol, ). Whilst these studies have generally shown positive interaction for effectiveness of FC in P fertilization, little is known about the direct effects of FC on microbial interactions and P availability in the sugarcane rhizosphere, which is the zone of soil where plants have large impact on soil processes (Pinton, Varanini, & Nannipieri, ).…”
Section: Introductionmentioning
confidence: 99%
“…Native vege- tation (seasonal semideciduous forest) soils were chosen to avoid residual effects of filter cake and vinasse application on soil properties [21] [22] [23]. These soils were sampled at the 0 -20 cm layer, air-dried, homogenized, and sieved to 2 mm before installing the experiment.…”
Section: Soils and Organic Residuesmentioning
confidence: 99%
“…Actual results in some studies showed the benefits of organomineral fertilization in agriculture, such as in the production of coffee crop (FERNANDES et al, 2007), the growth of rootstock 'Rangpur' lime (CARNEIRO et al, 2011), flower production (FARIAS et al, 2013) and sugarcane rations (SANTOS et al, 2014). However, the effect of fertilizer is linked to the fertilizer formulation and the species, or even the variety, that is being fertilized.…”
Section: Introductionmentioning
confidence: 99%